PERAN GURU DALAM MENDIDIK KEMANDIRIAN BELAJAR SISWA DI SMP MUHAMMADIYAH LUBUK PAKAM - Alfina Azisi BR Purba; Wahyudin Nur Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to identify the role of teachers in educating students' independent learning at Muhammadiyah Lubuk Pakam Middle School. The research method used is a qualitative research method with descriptive methods. This descriptive method allows researchers to describe in detail the role of teachers in educating students' independent learning through narrative data collection. The research results show that teachers at this school apply various strategies to encourage student learning independence. The main strategies implemented include careful learning planning, the use of learning methods that encourage interaction and problem solving, and the use of technology and innovative learning tools. Teachers also act as role models who demonstrate responsibility, independence, authority and discipline. To overcome barriers to learning, teachers create an interesting and relevant atmosphere, and provide support and guidance that suits each student's unique potential. It is hoped that parents will also play an active role in supporting their children's learning process at home. In conclusion, the role of teachers at Muhammadiyah Lubuk Pakam Middle School is very important in forming students' learning independence, helping them become independent, creative and critical thinking individuals.